THEORETICAL ASPECTS OF INTELLECTUAL PROPERTY RESEARCH UNDER THE MODERN CONDITIONS - A. A. Akhmetov (Russian Journal of Economics and Law)
The article analyzes the main theoretical approaches towards intellectual property in the modern economics. The main directions of this category research in western literature are viewed. The author distinguishes two vectors of analysis of intellectual property by Russian authors: as a specific category of property and as an object of institutional analysis. Paying special attention to the institutional approach, the author viewed the transactional costs which accompany the institution of intellectual property under the "new" economy.